HUBUNGAN RIWAYAT PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN STUNTING PADA ANAK USIA 7 – 36 BULAN DI DESA PAGOWAN PASRUJAMBE LUMAJANG - Handayani, Novi; Sary, Yessy Nur Endah; Zakiyyah, Muthmainnah (NHM PRESS, 2023)
Stunting increases the risk of morbidity and mortality as well as retards the growth of motor and mental abilities. Toddlers who are stunted have a risk of decreased intellectual abilities, productivity, and an increased risk of degenerative diseases in the future. The purpose of this study to analyze correlation history of exclusive breastfeeding and the incidence of stunting. This study used observational analytic design with cross-sectional approach. Data were taken from observation sheets which were carried out from May to June 2023 with population are 34 mothers giving birth and sample are 34 respondents using the total sampling technique. Data collection included coding, editing and tabulating. Bivariate analysis using chi square test showed a P-value = 0.000 < α 0.05, meaning that there was correlation hemoglobin levels and the length of labor in second stage. Odds ratio value of 9,500. This means that history of exclusive breastfeeding has risk of 9.5 times experiencing stunting. Suggestions put forward, research sites should conduct exclusive breastfeeding socialization to increase public knowledge.